The Role of Education in Promoting Gender Equality in Modern Society - Karim, Dudung Abdul; Pattiruhu, Claudia Monique; Chin, Jacky (MSJ : Majority Science Journal, 2024)
Education plays a very important role in forming an equal and just society, especially in promoting gender equality. In a modern society that is increasingly developing and plural, the issue of gender equality becomes very relevant, considering the persistence of gender inequality that still affects various sectors of life, such as economics, politics, and social. Therefore, education, both formal and non-formal, has great potential to address gender inequality and create a more inclusive society. Education not only functions as a means to gain knowledge, but also as an agent of social transformation that can shape individual views and behaviors towards gender issues. This article uses a Systematic Literature Review (SLR) approach to review the existing literature on the role of education in promoting gender equality. This study highlights various findings on how educational curricula, educational policies, and the role of educators can contribute to achieving gender equality. The results of this study indicate that although education has played an important role in promoting gender equality, there are still major challenges to be overcome, such as the influence of gender stereotypes in the curriculum, unequal access to education, and the lack of policies that support gender inclusivity in many countries.